The art book - Bugler, Caroline; Kramer, Ann; Weeks, Marcus; Whatley, Maud; Zaczek, Iain (New York, New York : DK Publishing, 2017)
Explores the ideas behind one hundred iconic works of art while examining their historical context.
SIBF2023
P.B
Includes bibliographical references (pages 350-351) and index.
Keywords: Art -- History; Art -- History; ART / Reference; ART / Subjects & Themes; Art; History